Reading Literacy Skills of Grade IV Students in Distance Learning - Monica Handayani; Risa Handini; Ristu Kinani; Raden Sudarwo (Jurnal Studi Guru dan Pembelajaran, 2024)
The importance of applying reading literacy skills as part of 21st-century skills is an inevitable necessity during the distance learning period in the COVID-19 pandemic. The test is needed to determine students' reading literacy skills so that teachers can develop evaluation tools that can be used to help develop students' reading literacy during the distance learning period. The test results serve as provisions for teachers to compile relevant learning activities and still equip students to improve reading literacy skills. This research design uses a single-subject design. This study aims to provide an overview of the reading literacy ability of grade IV elementary school students. The kind of study that was conducted in this study is non-experimental quantitative research with a descriptive form of research with the instruments used are the PIRLS reading ability test and questionnaire. Based on the results of the first reading ability test, showed that students' reading literacy during the distance learning period was in the medium category with a percentage of 59.3%, then the second test result showed a high category with a percentage of 44.44%. The results of the questionnaire from the PIRLS framework also showed similar results, namely 64% had reading comprehension skills and 68% of students were able to determine reading goals. These results prove that students' reading literacy skills during the distance learning period can still be improved by providing learning activities that make it easier for students to use reading materials at home properly.